Change of carrier spectrum in layer semiconductors caused by strong electromagnetic wave field - Lukiyanets, B.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Spectrum of carriers in layer semiconductors under action of strong electromagnetic field is analyzed. It is shown that obtained modification of the spectrum qualitatively differs from modification in analogous problem in excitonic dielectric or superconductor with the parabolic dispersion law of carriers.